On the Necessary Conditions for the Solubility of Algebraic Inverse Eigenvalue Problems (Journal of Computational Mathematics, 1992)
In this paper we give some necessary conditions for the solubility of additive inverse eigenvalue problems, multiplicative inverse eigenvalue problems and general inverse eigenvalue problems.